Reliability of manual segmentation of cornea, contact lens and tear film using a high-resolution OCT - Rodrigues, Patrícia (2015)
In this study, we aimed to evaluate the intra/inter-session and intra/inter-observer variability of manual segmentation of thickness of the pre-lens tear film, contact lens (CL), post-lens tear film, epithelium, bowman’s layer, stroma and the whole cornea and CLs with a flat and a steep fit, using a commercial high-resolution spectral domain optical coherence tomographer (OCT). Two different observers obtained three repeated measures in two separate sessions. A high correlation was found between the values obtained by the two different observers, except for the thinner layers, epithelium, and Bowman’s layer. Inter-observer analysis showed a high consistency in the measurements obtained by both observers (r 2 ≥ 0.80; p < 0.001) for the thicker layers: CL, stroma, and total cornea. Intra-observer analysis of measurements obtained by each observer within the same session displayed no statistically significant differences between the three repeated measures for both observers (p > 0.05). The present results suggest that manual segmentation of anterior segment OCT images in CL wearers provides acceptable levels of repeatability between observers and between different sessions for the thinner layers, while presenting a high level of repeatability for the thicker layers.